Validity and sensitivity to change of the falls efficacy scales international to assess fear of falling in older adults with and without cognitive impairment - Hauer, Klaus; Kempen, Gertrudis I. J. M.; Schwenk, Michael; Yardley, Lucy; Beyer, Nina; Todd, Chris; Oster, Peter; Zijlstra, G. A. Rixt (Gerontology, 2011)
Measures of fear of falling have not yet been validated in patients with dementia, leaving a methodological gap that limits research in a population at high risk of falling and fall-related consequences. The objectives of this study are to determine: (1) the validity of the 7-item Short Falls Efficacy Scale International (Short FES-I) in geriatric patients with and without cognitive impairment, and (2) the sensitivity to change of the 10-item Falls Efficacy Scale (FES), the 16-item FES-I and the 7-item Short FES-I in geriatric patients with dementia. Cross-sectional data of community-dwelling older adults and geriatric rehabilitation patients (n = 284) collected during face-to-face interviews were used to determine construct and discriminant validity by testing for differences within variables related to fear of falling. Sensitivity to change was studied in an intervention study including patients with mild to moderate dementia (n = 130) as determined by standard response means (SRMs). The Short FES-I showed excellent construct and discriminant validity in the total group and subsamples according to cognitive status. Sensitivity to change was adequate to good in the FES (range SRM: 0.18-0.77) and FES-I (range SRM: 0.21-0.74), with the Short FES-I showing the highest peak sensitivity to change (range SRM: 0.18-0.91). The Short FES-I is a valid measure to assess fear of falling in frail older adults with and without cognitive impairment, yet it may show floor effects in higher functioning older people. All scales, including the Short FES-I, were sensitive to detecting intervention-induced changes in concerns about falling in geriatric patients with dementia.
Gesehen am 07.09.2022